2022
DOI: 10.3138/cjhs.2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

HIV pre-exposure prophylaxis (PrEP) should be free across Canada to those meeting evidence-based guidelines

Abstract: HIV pre-exposure prophylaxis (PrEP) should be free across Canada for all those who meet evidence-based guidelines. PrEP is a highly effective tool for preventing HIV acquisition that has been approved for use in Canada since 2016. However, without public drug plans or private insurance, generic PrEP costs approximately $200 to $250 CAD monthly. Current PrEP programs across Canada are a confusing patchwork system with variability in coverage and prohibitive co-payments, making PrEP too expensive for many equity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Our model indicated that many eligible MSM were not engaged in PrEP care yet could have benefited from its use, as evidenced by their higher HIV incidence. The financial burden of PrEP in Montréal remains an important barrier, potentially leaving behind those most at risk of HIV acquisition [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our model indicated that many eligible MSM were not engaged in PrEP care yet could have benefited from its use, as evidenced by their higher HIV incidence. The financial burden of PrEP in Montréal remains an important barrier, potentially leaving behind those most at risk of HIV acquisition [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, understanding and navigating the medication coverage system in Canada can be confusing and discourage eligible GBM from using PrEP. 27 Costs of deductibles and pharmacy dispensing fees may have a further impact on the ability to access PrEP. Even in the setting of universally funded PrEP such as in BC, perceived cost may be a barrier if individuals are unaware of its availability.…”
Section: Discussionmentioning
confidence: 99%
“…24 , 25 Across Canada, approximately 60% of individuals have private medication coverage through employment. 26 Among insurers, there is considerable variation in the requirements and the extent to which drugs are subsidized, which has led some scholars to describe the current system as inefficient and as a “confusing patchwork.” 27 , 28 Furthermore, other groups, such as international students or visitors, do not have comprehensive medication coverage.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected as part of the PrEP Implemention Project (PRIMP), an ongoing mixed methods implementation science study with the overarching objective of understanding how to better deliver PrEP to GBQM in Ontario and British Columbia, Canada. [33][34][35]…”
Section: Study Settingmentioning
confidence: 99%